Prelingual Sensorineural Hearing Loss Caused by a Novel GJB2 Dominant Mutation in a Chinese Family. (22nd January 2020) - Huang, Shasha; Gao, Xue; Wang, Yufeng; Kang, Dongyang; Zhang, Xin; Yang, Suyan; Dai, Pu
Abstract : Background . GJB2 mutation is the most common cause of genetic deafness. Many pathogenic variations have already been identified, and thus, fewer and fewer novel pathogenic variations remain to be identified. Here, we describe a novel pathogenic variation associated with dominant hereditary deafness in a Chinese family. Methods . In this study, we examined four generations of a Chinese family (M127) with hearing loss. Temporal CT scan, complete physical examination (including skin and hair), and audiological tests were performed. Targeted next-generation and Sanger sequencing were used to identify pathogenic mutations in affected individuals. Results . All patients exhibited prelingual nonsyndromic sensorineural hearing loss, with severity ranging from moderate to severe. A novel dominant pathogenic variant c.205T > C (p.Phe69Leu) was identified in all patients in this family. Conclusions . c.205T > C (p.Phe69Leu) was identified as a novel dominant pathogenic variant of GJB2 associated with prelingual nonsyndromic sensorineural hearing loss.